2016
DOI: 10.15252/embj.201695081
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated SNARE s and specialized TRIM cargo receptors mediate secretory autophagy

Abstract: Autophagy is a process delivering cytoplasmic components to lysosomes for degradation. Autophagy may, however, play a role in unconventional secretion of leaderless cytosolic proteins. How secretory autophagy diverges from degradative autophagy remains unclear. Here we show that in response to lysosomal damage, the prototypical cytosolic secretory autophagy cargo IL-1b is recognized by specialized secretory autophagy cargo receptor TRIM16 and that this receptor interacts with the R-SNARE Sec22b to recruit carg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
319
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(328 citation statements)
references
References 98 publications
(227 reference statements)
8
319
1
Order By: Relevance
“…Purified eHAV preparations contained no detectable peptides derived from LC3, which in its lipidated LC3-II form is associated with autophagosome membranes. However, LC3 appears to be difficult to detect by mass spectrometry in autophagosome-derived extracellular vesicles (31,32). Nonetheless, eHAV vesicles were not precipitated by anti-LC3 antibody (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Purified eHAV preparations contained no detectable peptides derived from LC3, which in its lipidated LC3-II form is associated with autophagosome membranes. However, LC3 appears to be difficult to detect by mass spectrometry in autophagosome-derived extracellular vesicles (31,32). Nonetheless, eHAV vesicles were not precipitated by anti-LC3 antibody (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…For example, recruitment of the autophagy machinery by the activated AIM2 inflammasome has been proposed to mediate the release of IL-1β via exocytosis of the autophagosome [32]. Thus, IL-1β can be released in an autophagy-dependent manner that requires SNAREs and syntaxins [33]. Additional studies showed that autophagy is required for the release of active IL-1β or IL-18 downstream of other inflammasomes [34].…”
Section: Crosstalk Between Autophagy and The Inflammasome Machineriesmentioning
confidence: 99%
“…In future studies, it would also be of interest to evaluate whether other known key proteins involved in secretory autophagy, such as RAB8A (RAB8A, member RAS oncogene family) and GORASP2/GRASP55 (golgi reassembly stacking protein 2) [39,40], are implicated in PARK7 secretion, and whether 6-OHDA-induced secretory autophagy is implicated in the secretion of other proteins. It has been recently reported that dedicated SNAREs participate in secretory autophagy-mediated unconventional secretion of IL1B in response to lysosome damage [56]. Interestingly, secretion of IL1B depends on plasma membrane STX3 (syntaxin 3) and STX4 (syntaxin 4) instead of delivery to lysosomes via STX17 (syntaxin 17), which has been identified as a necessary protein for autophagosomal fusion with the endosome/lysosome [57].…”
Section: Discussionmentioning
confidence: 99%